Optimization Of Intensive Care For Nephro- And Hepatotoxicity Of Lung Cancer Chemotherapy (Eurasian Medical Research Periodical, 2026)
Lung cancer remains the leading cause of cancer mortality worldwide, and systemic chemotherapy is a cornerstone of treatment for advanced stages. However, many chemotherapeutic agents used in lung cancer can cause significant nephrotoxicity and hepatotoxicity, which may limit therapy, necessitate dose reductions, or even lead to lifethreatening organ failure. Cisplatin-based regimens, for example, are highly effective but carry a well-documented risk of acute kidney injury (AKI) due to proximal tubular damage, electrolyte disturbances, and reduced glomerular filtration. Likewise, various cytotoxic drugs can induce liver injury in idiosyncratic patterns ranging from transient asymptomatic transaminase elevations to fulminant hepatic failure. Optimizing intensive care management of these toxicities is essential to ensure patients can safely continue potentially curative treatments. This narrative review summarizes the nephrotoxic and hepatotoxic effects of common lung cancer chemotherapeutic agents and discusses strategies to prevent and mitigate these toxicities